NUTRITION, ANTHROPOMETRIC PARAMETERS AND MOTOR DEVELOPMENT OF PRESCHOOL (Fiep Bulletin - online, 2015)
Motor development is characterized by continuous changes over the life of the human being, and childhood is essential for the physical and motor development of the child stage. The aim of the study is to classify the level of maturation of motor patterns proposed by three tests (locomotion, manipulation and balance), establishing the percentage by gender and the difference in anthropometric variables between ages and sexes of children of kindergarten. It is a cross-sectional quantitative study, the main drivers were classified in early, elementary and mature on the critical development phase of directed walk, balance on one foot and bouncing stage of standard patterns. As a collection of variables (age, height and body mass) for calculating and classification of Body Mass Index (BMI), which consists of body weight (kg) divided by height 2 (m). The sample comprised 23 children of both sexes, aged between 4 and 6 years old. Data were tabulated using SPSS version 20.0, to compare gender and age with the variables: mass, height and BMI, we used the model analysis of variance (ANOVA) at 5% significance level. Directed to walk the boys had predominance in elementary and mature stages, while girls in elementary and early, to balance yourself on one foot were boys with the highest concentration in initial and mature with girls in elementary and mature already to the standard bounce the ball both sexes was early and elementary. It is concluded that results were expected in the literature for the development of the age group in question, except for the stage to bounce the ball level. No significant difference was found between sexes and ages for the variables body weight, height and BMI.
Keywords: motor development. BMI in childhood. Preschoolers.